Analysis of Parenting Style to Foster Children's Independencies in the Village Tanjung Jati District West Binjai - Rio Suparman; Yusnadi; Muhammad Takwin Machmud (International Journal of Educational Practice and Policy, 2024)
Children's independence is shaped and developed in large part by their parents, who help them to effectively navigate all of life's obstacles and conquer whatever obstacle they encounter. This study looks at the impact of parenting strategies in fostering children' independence. The method used in this research is a quantitative approach. The sample is involving 10 parents in Tanjung Jati village, West Binjai district. The data collection technique uses a questionnaire consists of 9 questions related to parenting and child independence. The survey results show that the majority of parents are considered to apply parenting styles that support children's independence, and parents assess their children as independent. In conclusion, the majority of parents employ a balanced parenting approach, which helps to foster children's progressive independence development..